Solid Polymer Electrolytes Based on Copolymers of Cyclic Carbonate Acrylate and n‐Butylacrylate. Issue 6 (24th February 2020) - Boujioui, Fadoi; Damerow, Helen; Zhuge, Flanco; Gohy, Jean‐François
Abstract: Solid polymer electrolytes (SPEs) are prepared by mixing poly(2‐oxo‐1, 3‐dioxolan‐4‐yl)methyl acrylate‐ random ‐ n ‐butylacrylate) [P(cyCA‐ r ‐ n BA)] statistical copolymers with bis(trifluoromethane)sulfonimide lithium salt. The P(cyCA‐ r ‐ n BA) copolymers are synthesized by reversible addition‐fragmentation chain transfer polymerization and different molar masses as well as copolymer composition are targeted in order to study the influence of the molecular parameters on the thermal, mechanical, and electrochemical properties of the SPEs obtained after mixing the copolymers with lithium salts. In the investigated experimental window, it is shown that the thermal and mechanical properties of the SPEs mainly depend on the composition of the copolymer and are poorly influenced by the molar mass. In sharp contrast, the ionic conductivities are more deeply influenced by the molar mass than by the composition of the copolymers. In this respect ionic conductivity values ranging from 4.2 × 10 −6 S cm −1 for the lower molar mass sample to 8 × 10 −8 S cm −1 for the higher molar mass one are measured at room temperature for the investigated SPEs. Abstract : Solid polymer electrolytes (SPEs) are prepared by mixing poly(2‐oxo‐1, 3‐dioxolan‐4‐yl)methyl acrylate‐ r ‐ n ‐butylacrylate) statistical copolymers with bis(trifluoromethane)sulfonimide lithium salt. Thermal and mechanical properties of the SPEs mainly depend on the composition of the copolymers while ionic conductivities are more deeply influenced by their molar mass.